Tuning the performance of Pt-Ni alloy/reduced graphene oxide catalysts for 4-nitrophenol reduction - Zhao, F.; Kong, W.; Hu, Z.; Liu, Jian; Zhao, Y.; Zhang, B. (Royal Society of Chemistry, 2016)
© 2016 The Royal Society of Chemistry. An environmentally benign and economic reaction system with an effective catalyst for 4-nitrophenol reduction is highly desirable. Here, we synthesized reduced graphene oxide (RGO) supported Pt-Ni alloy catalysts with different atomic ratios of Pt and Ni, investigated their morphology, size, dispersity, structure and elemental valence, and studied their catalytic activity in order to tune their performance for 4-nitrophenol reduction. It is worth pointing out that the RGO support can efficiently avoid the aggregation of Pt-Ni alloy nanoparticles, and the most dispersed and smallest Pt-Ni particles on RGO can be obtained when the atomic ratio of Pt to Ni is 1 : 9. The Pt-Ni/RGO (1 : 9) nanocatalyst also shows a higher catalytic activity toward the conversion of 4-NP to 4-AP with a catalytic rate constant of 0.3700 min-1than Pt-Ni/RGO (1 : 3) and Pt-Ni/RGO (1 : 25), and much higher than that of Pt/RGO, Ni/RGO and bare Pt-Ni owing to the well-defined composition, small particle size (10 nm), good dispersion, synergistic effect between Pt and Ni, and electron transfer between RGO and Pt-Ni alloy nanoparticles. In addition, the catalyst possesses good stability and recyclability for the catalytic reduction reaction. The Pt-Ni/RGO nanocatalyst, with well-defined composition, small particle size, uniform dispersity, high catalytic rate, and recyclability, should be an ideal catalyst for specific applications in liquid phase reactions.